2015
DOI: 10.1007/s11192-015-1624-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the degree to which articles supported by research grants are published in open access health and life sciences journals

Abstract: In the scientific publication world,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 11 publications
3
16
0
3
Order By: Relevance
“…They employ quantitative analyses with sample size ranging from around 100 to 2,000 journals. Most of the studies apply descriptive statistics and compare means, accompanied with scatter plots and histograms, while some also use correlation analyses (Bjoerk & Solomon, 2014Hagenhoff, Blumenstiel & Ortelbach, 2008;Pinfield, Salter & Bath, 2016Romeu et al, 2014;Solomon & Bjoerk, 2012aWang, Liu & Fang, 2015;Yuen, Muquit & Whitfield, 2018). More sophisticated data analyses are conducted by M. Smith et al (2016) and Schoenfelder (2018).…”
Section: Building Up Article Processing Chargementioning
confidence: 99%
See 1 more Smart Citation
“…They employ quantitative analyses with sample size ranging from around 100 to 2,000 journals. Most of the studies apply descriptive statistics and compare means, accompanied with scatter plots and histograms, while some also use correlation analyses (Bjoerk & Solomon, 2014Hagenhoff, Blumenstiel & Ortelbach, 2008;Pinfield, Salter & Bath, 2016Romeu et al, 2014;Solomon & Bjoerk, 2012aWang, Liu & Fang, 2015;Yuen, Muquit & Whitfield, 2018). More sophisticated data analyses are conducted by M. Smith et al (2016) and Schoenfelder (2018).…”
Section: Building Up Article Processing Chargementioning
confidence: 99%
“…Solomon and Bjoerk (2012b), Bjoerk and Solomon (2015), Pinfield et al (2017) and define journal quality as journal impact. Bjoerk (2012a), Yuen et al (2018), Romeu et al (2014), Bjoerk and Solomon (2014) and Wang et al (2015) study journal impact directly. Most of them employ the Journal Impact Factor (JIF) from Citation Reports (JCR) Web of Science (Romeu et al, 2014;Solomon & Bjoerk, 2012b;Wang et al, 2015).…”
Section: Building Up Article Processing Chargementioning
confidence: 99%
“…But instead of ranking journals based on a network of hyperlinks, Eigenfactor uses citations from the academic literature. Wang, Liu, and Fang (2015) analyzed the relationship between the Impact Factor and APC prices charged by open access journals in Health and Life Sciences indexed on the Web of Science database, attesting to a wide variation in the APC prices within similar Impact Factor ranges, from which we can deduce a low correlation between these variables. In Brazil, a system for journal classification -established by the regulatory agency of the national higher education system, National Council for Scientific and Technological Development (Capes, Coordenação de Aperfeiçoamento de Pessoal de Nível Superior) and acknowledged by the Brazilian scientific community -has been an alternative for the use of the aforementioned metrics.…”
mentioning
confidence: 99%
“…In the case of India, a substantial number of low-APC journals would have been used. Wang et al 22 have found that APC varies from region to region. European and North American APC OA journals have an average charge of more than US$ 2000, while Asian, African and South American APC OA journals have an average charge of less than US$ 1000 (ref.…”
Section: Potential Expenditure On Apc Seen In Perspectivementioning
confidence: 99%
“…European and North American APC OA journals have an average charge of more than US$ 2000, while Asian, African and South American APC OA journals have an average charge of less than US$ 1000 (ref. 22). …”
Section: Potential Expenditure On Apc Seen In Perspectivementioning
confidence: 99%